ANALISIS USAHA AGROINDUTRI PASTEL MINI BUDE PANDAU DI KECAMATAN SIAK HULU KABUPATEN KAMPAR PROVINSI RIAU - Arti Marni; Septina Elida (UIR Press, 2023)
Agroindustry is one of sub-systems in agribusiness and an integration form between the industrial and agricultural sectors. Agrifood is one of the industries that is developing today. The agro-industry that is developing in Kecamatan Siak Hulu is the agro-industry of pastel mini bude pandau. This study aims to analyze the characteristics of entrepreneurs and business profiles of Pastel Mini Bude Pandau, Siak Hulu District, Kampar Regency, Riau Province, dan production costs, production, income, efficiency, and added value in the Mini Bude Pandau Pastel Business in Siak Hulu District, Kampar Regency, Riau Province. The data collected consisted of primary and secondary data. The analysis used is descriptive, quantitative, and qualitative statistics technique. The aspects studied are the use of production factors, production technology, production costs, production, income, efficiency (RCR), and added value. The results showed that the pandau mini bude pastel agro-industry business has been established since 2012 and is a family business. The industry is now the second generation with a capital of Rp. 15,000,000 (excluding land and buildings). Characteristic entrepreneur was 49 years of age, 9.8 years of education level (equivalent to junior high school), and 10 years of business experience. The age characteristics of workers was an average of 41.41 years. The technology used in the mini pastel agro-industry to produce output was semi-technology level. The raw materials is 60 kg/process, and agro-industrial production costs are IDR 3,485,667/production process with a total production of 200 kg/production process. The gross income was Rp 6.200.000/production process and net income was Rp 2. 714,333/production process. Efficiency (RCR) was 1.78. The added value obtained from mini pastel processing per production process is IDR 88.005,33 with an added value ratio of 85,16%.